PENGARUH OUTSERT TERHADAP ALIRAN DAN PERPINDAHAN KALOR PADA ANNULAR HEAT EXCHANGER TIPE HORIZONTAL - Ma'a, Mustaza; Kamal, Samsul; Pranoto, Indro (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
In the industrial environment, there is a need to boost heat transfer. The flow manipulation method was selected because it is less expensive, simpler to use, and more accessible. It is wise to utilize a horizontal type annular heat exchanger because it is simple and easy to manufacture. Cold fluid from the reservoir tank is pumped through the annulus in a closed system. Cold fluid passes through the Omega rotameter before it enters the experiment apparatus. The cooling system allows cold fluid to leave through the outlet and return to the reservoir tank. There are five different cold fluid flow rates, ranging from 2.5 GPM to 5 GPM. A tubular heater with a 500 W heat rate is inserted in the annular heat exchanger's midsection. The flow inside the annulus is heated by this heater. According to the results of the experiments, utilizing outsert has the potential to increase the heat transfer coefficient (h) average 89,84%, Nusselt number (Nu) average 76,76%, and friction factor (f) average 55,48%. The flow regime, which starts out in laminar circumstances and transition to quasi-turbulent and turbulent conditions at Re = 8000, is also impacted by the presence of an outsert. The thermal performance factor (η) average 1,54, which demonstrates an increase in heat transfer.